Workplace health promotion and safety in state and territorial health departments in the United States: a national mixed-methods study of activity, capacity, and growth opportunities - Laura A. Linnan; Maija S. Leff; Marisa C. Martini; AnnMarie L. Walton; Sherry Baron; Peggy A. Hannon; Jean Abraham; Melanie Studer (BMC, 2019)
Abstract Background State and Territorial Health Departments (SHDs) have a unique role in protecting and promoting workers' health. This mixed-methods study presents the first systematic investigation of SHDs' activities and capacity in both Occupational Safety and Health (OSH) and Workplace Health Promotion (WHP) in the United States (US). Methods National survey of OSH and WHP practitioners from each of 56 SHDs, followed by in-depth interviews with a subset of survey respondents. We calculated descriptive statistics for survey variables and conducted conventional content analysis of interviews. Results Seventy percent (n = 39) of OSH and 71% (n = 40) of WHP contacts responded to the survey. Twenty-seven (n = 14 OSH, n = 13 WHP) participated in follow-up interviews. Despite limited funding, staffing, or organizational support, SHDs reported a wide array of activities. We assessed OSH and WHP surveillance activities, support that SHDs provided to employers to implement OSH and WHP interventions (implementation support), OSH and WHP services provided directly to workers, OSH follow-back investigations, and OSH standard and policy development. Each of the categories we asked about (excluding OSH standard and policy development) were performed by more than half of responding SHDs. Surveillance was the area of greatest OSH activity, while implementation support was the area of greatest WHP activity. Respondents characterized their overall capacity as low. Thirty percent (n = 9) of WHP and 19% (n = 6) of OSH respondents reported no funds at all for OSH/WHP work, and both groups reported a median 1.0 FTEs working on OSH/WHP at the SHD. Organizational support for OSH and WHP was characterized as "low" to "moderate". To increase SHDs' capacity for OSH and WHP, interview respondents recommended that OSH and WHP approaches be better integrated into other public health initiatives (e.g., infectious disease prevention), and that federal funding for OSH and WHP increase. They also discussed specific recommendations for improving the accessibility and utility of existing funding mechanisms, and the educational resources they desired from the CDC. Conclusions Results revealed current activities and specific strategies for increasing capacity of SHDs to promote the safety and health of workers and workplaces - an important public health setting for reducing acute injury and chronic disease.